Data extraction for scale factor determination used in 3D-photogrammetry for plant analysis - Achanta, Leela Venkata Naga Satish (Kansas State University, 2013)
ImageJ and its recent upgrade, Fiji, are image processing tools that provide extensibility via Java plug-ins and recordable macros [2]. The aim of this project is to develop a plug-in compatible with ImageJ/Fiji, which extracts length information from images for scale factor determination used in 3-D Photogrammetry for plant analysis [5]. Plant images when processed using Agisoft software, gives an image consisting of the images processed merged into a single 3-D model. The coordinate system of the 3-D image generated is a relative coordinate system. The distances in the relative coordinate system are proportional to but not numerically the same as the real world distances. To know the length of any feature represented in 3-D model in real world distance, a scale factor is required. This scale factor when multiplied by some distance in the relative coordinate system, yields the actual length of that feature in the real coordinate system. For determining the scale factor we process images consisting of unsharpened yellow colored pencils which are all the same shape, color and size. The plug-in considers each pencil as a unique region by assigning unique value and unique color to all its pixels. The distance between the end midpoints of each pencil is calculated. The date and time on which the image file gets processed, name of the image file, image file creation and modification date and time, total number of valid (complete) pencils processed, the midpoints of ends of each valid pencil, length (distance) i.e., the number of pixels between the two end midpoints are all written to the output file. The length of the pencils written to the output file is used by the researchers to calculate the scale factor. Plug-in was tested on real images and the results obtained were same as the expected result.
Keywords: Calibration; Scale factor; ImageJ/Fiji; Plug-in; 3D photogrammetry; Plant analysis; Computer Science (0984)